Leadership and Change Management in a Rapidly Changing Environment - Subramoney, S.; Matshabaphala, M. D. J. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
The Heads of Departments (HoDs) in the South African public sector are appointed on a five-year contract and not on a permanent capacity and there is also a high turnover of HoDs. The frequent change of HoDs is further exacerbated by the rapid changes taking place in the environment, which means that change management has to be implemented fast and efficiently, any delay or disruption can have an adverse effect on the change process. The purpose of this research was to investigate the effect that the high turnover rate of HoDs in the South African public sector has on maintaining the momentum at which government programmes are being undertaken specifically focusing on the implementation of the Outcomes Approach. The Presidency in South Africa implemented the Outcomes Approach in 2010, which monitors government performance in the country. The intention of the Outcomes Approach is to enhance service delivery, therefore all government departments in the country have a role to play in the Outcome Approach. As with any new project or programme, there is the need for a rigorous change management process with committed and supportive leadership. This research study looked at how change management was implemented and sustained, for the Outcomes Approach, with the frequent change of leadership. A qualitative approach was used for this research. The findings showed that in some cases the change of HoD influenced the department in a positive manner while in other cases it had negative results. Change management was conducted, to varying extents as there was more reliance on the National Development Plan. Most change management models were developed before the onset of rapid change and frequent change of HoDs; therefore, the Triple I Change Management Model was developed for this study where there is frequent change of leadership in a rapidly changing environment.
Article published in the 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Change management; Frequent change of leadership; Outcomes approach; Rapidly changing environment; Organizational change--Management